2011
DOI: 10.1029/2010wr009697
|View full text |Cite
|
Sign up to set email alerts
|

Relating climatic attributes and water resources allocation: A study using surface water supply and soil moisture indices in the Snake River basin, Idaho

Abstract: [1] Climate change forced by anthropogenic activities has been ongoing since at least the beginning of the industrial revolution. Part of the recent warming in the western United States has been attributed to anthropogenic climate change. This research seeks to answer the basic question of how declining streamflow, increasing temperatures, and fluctuation in precipitation have impacted water resource allocation in the Snake River Plain over the past 35 years . Understanding how changes in climatic attributes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 66 publications
(67 reference statements)
0
33
0
Order By: Relevance
“…Although this method removes the need for iterative flood control and the use of a perfect forecast, it assumes no major shift in precipitation patterns. An analysis of historic precipitation trends in the Snake River basin between 1971 and 2005 indicate minimal shifts in seasonal precipitation (Hoekema and Sridhar, ). Studies by Mote et al .…”
Section: Model Development Calibration and Validationmentioning
confidence: 99%
“…Although this method removes the need for iterative flood control and the use of a perfect forecast, it assumes no major shift in precipitation patterns. An analysis of historic precipitation trends in the Snake River basin between 1971 and 2005 indicate minimal shifts in seasonal precipitation (Hoekema and Sridhar, ). Studies by Mote et al .…”
Section: Model Development Calibration and Validationmentioning
confidence: 99%
“…Another study by Hoekema and Sridhar () utilized a stepwise relationship that is revealed by plotting SWSI values vs . diversion rates for canals across the Snake River from 1971 to 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Hoekema and Sridhar (2011) utilized a stepwise relationship that is revealed by plotting SWSI values vs. diversion rates for canals across the Snake River from 1971 to 2005. As water supply (or SWSI value) increased, diversions increased until a threshold was reached.…”
Section: Introductionmentioning
confidence: 99%
“…During drought, farmers in primarily rain-fed areas may implement short-term irrigation (i.e., a LULCC) to increase soil moisture, which puts pressure on regional aquifers and surface water sources [82,83]. These irrigation practices are a key management response to drought conditions [84], but they alter the landscape pattern (e.g., through creating CPI) in a manner that affects the entire hydrologic processes [85,86], which has an important impact on water cycling and community dynamics [87]. We test the relationship between CPI and groundwater recharge to establish a linkage between the pattern and process.…”
Section: Linking Landscape Patterns To Ecological Processesmentioning
confidence: 99%